Incidence of Ototoxicity in Pediatric Patients with Transfusion-Dependent Thalassemia Who Are Less Well-Chelated by Mono- and Combined Therapy of Iron Chelating Agents. (October 2014) - Tanphaichitr, Archwin; Kusuwan, Thisarat; Limviriyakul, Siriporn; Atipas, Suvajana; Pooliam, Julaporn; Sangpraypan, Tuangrat; Tanphaichitr, Voravarn S.; Viprakasit, Vip
Abstract Ototoxicity due to iron chelation therapy, especially deferoxamine (DFO), is frequently observed in patients who have a higher chelation index (>0.025). However, there is limited data on patients who are less well-chelated and on other chelating regimens, including deferiprone (L1), deferasirox (DFX), and a combination of DFO and L1. To determine the incidence of ototoxicity from iron chelators, we retrospectively analyzed our clinical records from January 1997 to December 2010. All transfusion-dependent thalassemia (TDT) patients received iron chelation therapy with mono DFX, DFO, L1, or a combination. All patients underwent routine otolaryngologic examination and pure-tone audiometry before starting each chelation regimen and were regularly followed every 6 months. One hundred thalassemic patients were enrolled and analyzed (48 males and 52 females), with a mean age of 12.11 ± 4.48 years (range 2.5–22.5 years). Total summative duration of iron chelation therapy in all patients was 596.50 years. Nine patients were found to have conductive hearing loss. Sensorineural hearing loss (SNHL) was identified in seven patients but only four were determined to be associated with iron chelators; three patients were detected while undergoing DFO therapy and one patient with L1 therapy. None of patients undergoing DFO therapy had reached over the levels of chelation index. In our resource-limited setting with poor treatment compliance, there was a rather low incidence of ototoxicity after exposure to iron chelators. However, a routine audiometry remains recommended for early detection and intervention since SNHL still develops and results in a long-term morbidity.